Reflection on the Use of Galactagogues (Both Chemical and Herbal) in Increasing Breast Milk Production in the Pontang Community Health Center Working Area - Agus Sustiyono; Innama Sakinah; Fifi Musfirowati; Ahmad Jubaedi; Lia Nurliana (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Based on data from the Banten Provincial Office, the coverage of exclusive breastfeeding in Banten Province in 2017 was 75.7%, which did not meet the target set in 2016 in Banten Province (77%). The suboptimal rate of exclusive breastfeeding may be due to the low amount of breast milk produced by mothers. This study was conducted to determine the benefits of chemical galactagogues and herbs in increasing breast milk production in the Pontang Community Health Center working area. The population in this study consisted of 32 breastfeeding mothers with children aged 0-6 months in the Pontang Community Health Center working area, comprising 16 chemical and 16 herbal mothers. This study will be conducted in May-June 2024 at the Pontang Community Health Center. Methods: The research method used is a quasi-experiment with a cross-sectional approach. Data collection was carried out using breast milk pumps and breast milk bags. The data were then analyzed using univariate and bivariate (influence analysis) methods. Results: The results showed a significant p-value of 0.000 between galactagogues and increased breast milk production in the chemical intervention group compared to the herbal intervention group. Conclusions: The paired sample T-test showed a difference in mean values between the chemical intervention group and the herbal intervention group of 12.18, which means that the average breast milk production in the herbal group was much greater than the average breast milk production in the chemical group. It is hoped that health workers can provide information and disseminate or provide counseling when conducting practical visits about the benefits of galactagogues to the community, especially breastfeeding mothers.